Vendor assessment: a computerised approach. (4th August 2014) - Stainer, Alan; Ghobadian, Abby; Liu, Jonathan; Kiss, Tebor
The purchasing function is of vital importance in manufacturing because materials and components form a significant part of product costs. Vendor assessment provides management with a powerful control tool. The gleaned information is both useful in negotiations with suppliers and in contributing towards the establishment of closer links. This article discusses the state of the art of vendor rating and gives details of a flexible programme designed to make the assessment system more relevant and effective. The programme can also be employed to assist in the supplier evaluation and qualification processes.